Pelatihan Entrepreneurship Bagi Generasi Milenial Untuk Mendorong Pengembangan Ekonomi Bangsa Berbasis Ekonomi Digital - Ilyas Ilyas; Syamsir Nur; Isalman Isalman (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2022)
The Covid-19 pandemic is not only a challenge but also an opportunity for every nation. This pandemic has opened up opportunities for accelerating digital business growth. One of the keys to success in building a digital business is the increasing number of millennials who are entering into entrepreneurship. However, the reality in this country shows that there is still a lack of young people who become entrepreneurship. Among the variables that cause it are the lack of knowledge about entrepreneurship, not having business capital and the mindset to always want to be an employee or employee. The solution offered to overcome this problem is to conduct entrepreneurship training. With this training, it will provide understanding to the millennial generation about entrepreneurship so that in the end it will encourage them to become entrepreneurs.